Niveles de violencia intrafamiliar en adolescentes con consumo de sustancias psicoactivas - Casseres Palomino, Francelis Elena (Psicología, 2017)
This work of research entitled "levels of violence domestic in adolescents with consumption of substances psychoactive in two institutions of the city of Cartagena of Indian, has as purpose describe the presence of violence domestic in them adolescents." Will demonstrate various problem in the family educational and sociocultural. In reference to this, is took a population object of study comprised by 72 adolescents in ages of 14 and 17 years where the majority of these young not is were school. For this reason, it is convenient to develop this since project which allows you to address an issue that influences the well-being. The methodology used was through the research quantitative descriptive, where is applied the instrument questionnaire from exposure to the violence of Orue and Calvete (2010). Is conducted review literature highlighting authors as Ledoux, Quezada, Florez, among others. For this research raised the following question would what are the levels of violence domestic in adolescents with consumption of substances psychoactive in two institutions of the city of Cartagena of Indian? Highlighting results as the receptivity of adolescents in the implementation of the questionnaire of exposure to violence, obtaining as a result that the majority of these young people are exposed to domestic violence. In conclusion, is evidence that and of the causes of the violence domestic is the consumption de substances psychoactive.